Pengaruh Persepsi Kemudahan, Persepsi Kebermanfaatan, dan Kualitas Informasi terhadap Minat Masyarakat Kota Bogor dalam Penggunaan Layanan Telemedicine (Studi Pada Pengguna Aplikasi Halodoc, Alodokter, Yesdok) - Hapsari, Nurma Murti; Prawiradilaga, R. Rizky S; Muhardi, Muhardi (Jurnal Nasional Manajemen Pemasaran dan SDM, 2023)
The use of information systems in Indonesia has been widely used in various fields, especially in the health sector, the use of information technology in the world of health is the emergence of telemedicine applications that can facilitate the process of interaction between doctors and patients. The purpose of this study was to analyze the effect of perceived convenience, perceived usefulness and quality of information on the interest of the people of Bogor city in using telemedicine services. This research method uses quantitative methods with explanatory research. The research was carried out in the people of Bogor City who used the Halodoc, Alodokter and YesDok applications with a research sample of 121 respondents. The analysis technique applied is multiple regression analysis. The results showed that perceived convenience had a positive and significant effect on user interest with a significance value of 0.000 <0.05 and t count > t table 4.126> 1.9801, perceived usefulness had a positive and significant effect on user interest with a significance value and t count > t table 3.979> 1.9801, the quality of information has a positive and significant effect on interest in use with a significance value and t count > t table 4.442> 1.9801 and simultaneously perceived ease, perceived usefulness and quality of information affect user interest with a significance value and the calculated f value > f table 73.584> 1.9801. This study concludes that perceived of ease of use, usefulness, and quality of information affect people's interest in using telemedicine services.